The Incidence and Risk Factors for Surgical Site Infection: A Prospective Cohort Study - Patel, Lopa; Chauhan, Arjun; Ashai, Anha; Basilio Corage, Surene De Fatima; Rathwa, Chhayankaben; Chauhan, Anjali (Journal of Neonatal Surgery, 2025)
Background: Surgical site infections (SSIs) are a major cause of postoperative morbidity in orthopaedic surgery, particularly in low-resource settings. Identifying risk factors associated with SSIs is critical for improving patient outcomes and guiding infection control strategies. Objective: To determine the incidence and explore risk factors contributing to SSIs among orthopaedic patients undergoing surgery at Parul Sevashram Hospital, Vadodara, Gujarat. Methods: A prospective cohort study was conducted on 100 patients aged ≥18 years who underwent orthopaedic surgery between July 2022 and July 2023. Data on demographic, preoperative, intraoperative, and postoperative factors were collected using a structured tool. Statistical analysis was performed using SPSS version 25. Chi-square tests were used to determine associations between variables and SSIs. Results: The overall incidence of SSIs was 13%. Significant demographic risk factors included age (p=0.038), education level (p=0.023), rural residence (p=0.025), and alcohol consumption (p=0.005). Preoperative factors such as trauma (p=0.001) and deformity (p=0.029) were significantly associated with SSIs. Among intraoperative factors, the surgical site (upper vs. lower limb) showed a significant association (p=0.011). Postoperative factors, including drain fluid volume (p=0.001), number of drainage days (p=0.001), and length of hospital stay (p=0.002), were also significantly associated with SSIs. Conclusion: The study identified a relatively high incidence of SSIs and several associated risk factors in orthopaedic patients. Targeted interventions focusing on modifiable factors—particularly in the preoperative and postoperative phases—are essential to reduce infection rates and improve surgical outcomes.